ChemInform Abstract: Facile Synthesis of Hybrid Core—Shell Nanospheres for the Asymmetric Transfer Hydrogenation of Aromatic Ketones. Issue 40 (30th September 2014) - Wei, Juan; Zhang, Xiaomin; Zhang, Xiaoming; Zhao, Yaopeng; Li, Ruixiang; Yang, Qihua
Abstract Aryl methyl ketones and α, β‐unsaturated ketones are reduced stereoselectively to secondary alcohols in the presence of Rh‐functionalized hybrid core—shell nanospheres.